Demographic profile of offenders in long-term disciplinary segregation - Davis, E. Duane (American journal of criminal justice, 1985)
This paper seeks to identify inmate demographic characteristics which may help to classify troublemaking offenders. Data were obtained from the Georgia Department of Offender Rehabilitation for all adult male inmates completing the diagnostic process between 1971–1978 (n=19,363). For purposes of analysis, this population was then dichotomized into those inmates who had required longterm disciplinary segregation and those who had not. Analysis of these data revealed statistically significant differences between the two groups on numerous demographic variables including sentence length, crime type, selfreported education, and prior living arrangement.